Modelling proof-of-work agreement protocol by coloured Petri nets. Issue 6 (2nd November 2022) - Pröll, Birgit; Retschitzegger, Werner; Schwinger, Wieland; Shmeleva, Tatiana R.; Zaitsev, Dmitry A.
Abstract : Proof-of-work agreement protocol, offered by Keller and Böhme, is analysed by coloured Petri nets and refined. Blockchain technology, based on proof-of-work procedure and Nakomoto consensus negotiations, represents fundamentals of many kinds of cryptocurrency widespread recently. The protocol, called A k, works in continuous time which is simulated using random exponential distribution function of CPN Tools system, obtained values rounded to map them into discrete time of a coloured Petri net. Hierarchical model consists of an environment subnet and a given number of nodes communicating via an unstructured network represented by a single place; the model of node is further structured based on event handlers of the protocol source specification such as initialisation, activation, message delivering, and termination condition check. Based on the simulation results, modifications of the protocol and its parameters are recommended which improve some imperfections of the protocol. GRAPHICAL ABSTRACT: UF0001